Answer:
(f-g)(x)= -2x
(f.g)(x)= 3x^2 + 8x +4
(f+g)(-1)=0
Step-by-step explanation:
Given:
f(x) = x + 2
g(x) = 3x + 2
(f-g)(x)=?
(f.g)(x)=?
(f+g)(-1)=?
The expression for (f-g)(x) is:
(f(x)-g(x))(x) = (x + 2) - (3x + 2)
=x+2-3x-2
Simplify
(f(x)-g(x))(x) = -2x
The expression for (f.g)(x) is:
![\begin{gathered} (f(x)\cdot g(x))(x)=(x+2)(3x+2)_{} \\ We\text{ use FOIL method:} \\ (a+b)(c+d)=ac+ad+bc+bd \\ Let\text{: } \\ a=x \\ b=2 \\ c=3x \\ d=2 \\ So, \\ =(x)(3x)+(x)(2)+(2)(3x)+(2)(2) \\ \text{Simplify} \\ =3x^2+2x+6x+4 \\ (f(x)\cdot g(x))(x)=3x^2+8x+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bss97v4opi71vxenqmphgeb7yrtm8n5o8w.png)
And, the evaluation for (f+g)(-1) is:
(f(x) +g(x))(-1) = ((x + 2)+(3x + 2))(-1)
This means we let x= -1.
We plug in what we know:
=x + 2+3x + 2)
=-1+2+3(-1)+2
Simplify:
=-1+2-3+2
=-4+4
(f(x) +g(x))(-1) = 0
Therefore:
![\begin{gathered} \mleft(f\mleft(x\mright)-g\mleft(x\mright)\mright)\mleft(x\mright)=-2x \\ (f(x)\cdot g(x))(x)=3x^2+8x+4 \\ \mleft(f\mleft(x\mright)+g\mleft(x\mright)\mright)\mleft(-1\mright)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zzyap2v5ugz6yc013rw8cbame63g6bc506.png)